(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A survey of the development of trade unions in India shows that most of the unionsare affiliated with either of the four central trade union federations, viz.,Indian National Trade Union Congress, All India Trade Union Congress, HindMazdoor Sabha and United Trade Union Congress. Besides these some of the tradeunions are affiliated with seven other trade union federations, viz., BhartiyaMazdoor Sangh, Hind Mazdoor Panchayat, Centre of Indian Trade Union, NationalFederation of Independent Trade Unions, National Labour Organization, TradeUnion Coordination Committee and United Trade Union Congress (Lenin Sarani).These trade union organizations have been patronized by different politicalparties in the country. Further, a survey of the trade unions in India revealsthat over the years the trade union movement has undergone significantdevelopment. Both workers and non-workers have been involved. The beginnings ofthe movement were the outcome of the efforts made by certain social reformersand labour leaders. “The early... trade union movement (was) often full ofdifficulties. Strike committees (arose) calling themselves trade unions anddemanding the privileges of trade unions, without any means of discharging theresponsibilities thereof.